Design, Synthesis, and Computational Evaluation of 3,4-Dihydroquinolin-2(1H)-One Analogues as Potential VEGFR2 Inhibitors in Glioblastoma Multiforme - Shafeek Buhlak; Nadeem Abad; Jihane Akachar; Sana Saffour; Yunus Kesgun; Sevval Dik; Betul Yasin; Gizem Bati-Ayaz; Essam Hanashalshahaby; Hasan Türkez; Adil Mardinoglu (Pharmaceuticals)
Background/Objectives: Glioblastoma multiforme (GBM), an aggressive and deadly brain tumour, presents significant challenges in achieving effective treatment due to its resistance to current therapies and poor prognosis. This study aimed to synthesise and evaluate 23 novel analogues of 3,4-dihydroquinolin-2(1H)-one, designed to enhance druggability and solubility, and to investigate their potential as VEGFR2 inhibitors for GBM treatment. Methods: The synthesised compounds were analysed using in silico methods, including molecular docking and dynamics studies, to assess their interactions with key residues within the VEGFR2 binding pocket. In vitro evaluations were performed on U87-MG and U138-MG GBM cell lines using MTT assays to determine the IC50 values of the compounds. Results: Among the tested compounds, 4u (IC50 = 7.96 μM), 4t (IC50 = 10.48 μM), 4m (IC50 = 4.20 μM), and 4q (IC50 = 8.00 μM) demonstrated significant antiproliferative effects against both the U87-MG and U138-MG cell lines. These compounds exhibited markedly higher efficacy compared to temozolomide (TMZ), which showed IC50 values of 92.90 μM and 93.09 μM for U87-MG and U138-MG, respectively. Molecular docking and dynamics studies confirmed strong interactions between the compounds and VEGFR2 kinase, supporting their substantial anti-cancer activity. Conclusions: This study highlights the promising potential of 3,4-dihydroquinolin-2(1H)-one analogues, particularly 4m, 4q, 4t, and 4u, as VEGFR2-targeting therapeutic agents for GBM treatment. Further detailed research is warranted to validate and expand upon these findings.